GMA Spot Welding of A7075-T651/AZ31B Dissimilar Alloys using Stainless Steel Filler - M., Ishak; M. Rafiqul, Islam; Toshiyuki, Sawa (Taylor & Francis, 2014)
The aim of this research was to investigate the welding joint's fracture toughness and fracture surface morphologies between A7075-T651 aluminum and AZ31B magnesium dissimilar alloys welded using a new technique of gas metal arc spot lap welding with unconventional ER308L-Si stainless steel filler. The fracture toughness of the welding joints was estimated from yield strength and absorbed charpy impact energy of the joints using Rolfe-Novak-Barsom correlation, and was compared with the fracture toughness of AZ31B parent metal. Fracture surface morphologies were investigated by scanning electron microscopy. The results showed that the joint can achieve a maximum fracture toughness of 93.08% of the AZ31B parent metal. Most of the joints failed at AZ31B alloy, while some failed at A7075-T651 alloy and ER308L-Si nugget. Brittle fracture mechanism was observed for all the joints. It was found that the new gas metal arc spot lap welding technique with ER308L-Si filler could offer very good mechanical properties.